THE IMPACT OF EMPLOYEE MOTIVATION ON ORGANISATION PERFORMANCE OF TORORO CEMENT INDUSTRY - Gidudu,charles (Uganda christian university, 2024)
This study investigated the impact of various motivational factors on employee performance at Tororo Cement Limited, with a focus on allowances, non-monetary rewards, and attractive salaries. The research aimed to examine the effects of these factors on employee achievement of organizational goals, effectiveness, and efficiency. The targeted population consisted of 260 employees, out of which 103 responded, providing data through interviews and focus group discussions. The findings indicated that allowances, particularly for transport (69.6%), housing (60.1%), and medical expenses (53.8%), significantly contribute to employees' motivation by reducing their personal financial burdens, thereby enhancing their focus on achieving organizational goals. Non-monetary rewards, such as a positive work environment (75.9%), recognition (65.2%), and career development opportunities (50.6%), were also found to play a crucial role in improving employee effectiveness. Additionally, a strong positive relationship was identified between attractive salaries and employee efficiency, with 57.0% of respondents perceiving their salaries as fair and competitive, leading to increased commitment and productivity. The study concluded that a balanced approach incorporating both financial incentives and non-financial rewards is essential for enhancing employee motivation and performance. Recommendations included regular review and adjustment of allowances and salaries, fostering a positive work environment, implementing recognition programs, and providing career development opportunities. Future research could further explore the long-term impacts of these motivational strategies on employee retention and organizational performance.